2015
DOI: 10.1002/hep.27671
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno‐associated virus–mediated inhibition of microRNA‐21 protects mice against the lethal schistosome infection by repressing both IL‐13 and transforming growth factor beta 1 pathways

Abstract: Schistosomiasis is a serious parasitic disease in humans, which can lead to liver fibrosis and death. Accumulating evidence indicated that targeting the deregulated microRNAs could mitigate disease outcomes. Here, we showed that progressive hepatic schistosomiasis caused elevation of miR-21 and efficient and sustained inhibition of miR-21 by using highly hepatic tropic adeno-associated virus serotype 8 (rAAV8) protected mice against the lethal schistosome infection through the attenuation of hepatic fibrosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 30 publications
5
79
0
Order By: Relevance
“…Researchers have found that the IL-13/miR-21/Smad7 signaling interactions in hepatic stellate cells are equally important in the two signaling pathways that can influence the formation of collagen and play an important role in the development of schistosome-induced hepatic fibrosis (27). The receptors (IL-13R␣1/IL-4R␣) on hepatic stellate cells were stimulated by IL-13 through Smad1/2 (Smad1/5 and Smad2/3) phosphorylation (7), positively regulating production of miR-21 and then interfering with the target genes of miR-21 and Smad7 and subsequently preventing Smad7 from negative-feedback regulation of Smad1/2 (Smad1/5 and Smad2/3).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that the IL-13/miR-21/Smad7 signaling interactions in hepatic stellate cells are equally important in the two signaling pathways that can influence the formation of collagen and play an important role in the development of schistosome-induced hepatic fibrosis (27). The receptors (IL-13R␣1/IL-4R␣) on hepatic stellate cells were stimulated by IL-13 through Smad1/2 (Smad1/5 and Smad2/3) phosphorylation (7), positively regulating production of miR-21 and then interfering with the target genes of miR-21 and Smad7 and subsequently preventing Smad7 from negative-feedback regulation of Smad1/2 (Smad1/5 and Smad2/3).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that miRNAs play a crucial role in many human diseases including schistosomiasis (He et al, 2013, He et al, 2015, Cai et al, 2013, Cai et al, 2016, Han et al, 2013). Our previous study using miRNA microarrays demonstrated that a series of miRNAs were deregulated in the progression of hepatic schistosomiasis in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study using miRNA microarrays demonstrated that a series of miRNAs were deregulated in the progression of hepatic schistosomiasis in a mouse model. Importantly, miR-21, one of the upregulated miRNAs, was involved in the regulation of activation of hepatic stellate cells (HSCs) and downregulation of miR-21 prevented lethal infection by repressing both TGF-β1 and IL-13 pathways (He et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, miR-21 has been ascribed a crucial role in the regulation of cellular activity during physiological and pathological processes [31]. miR‑21 is widely expressed and has been found to be increased in organs and tissues which have suffered fibrogenesis or remodeling, including the heart [32], kidney [33], lung [34], asthmatic airways [35, 36], liver [37, 38], skin [39-41], and tumor tissue [42, 43]. Studies revealed that enhanced miR-21 expression is involved in the progression of lung fibrosis, and TGF-β1 plays an important role in mediating increased miR-21 expression [34, 44].…”
Section: Introductionmentioning
confidence: 99%